O56. The Cape Town Access to Care course, our ongoing teaching journey. (September 2016) - Parkes, J.; Burger, H.; Wyrley-Birch, B.; Valentim, J.-M.; Groll, J.
Abstract : Introduction: Access to radiotherapy treatment units, treatment planning systems and appropriate dosimetry equipment is an ongoing challenge throughout Africa. This is coupled with a need for the implementation of 3-D conformal therapy protocols and likewise the appropriate skills training for staff. The Access to Care centre based at Groote Schuur Hospital is designed to be an innovative technology-based teaching platform for the radiation oncology treatment team, namely: radiation oncologists (RO), medical physicists (MP) and radiation therapists (RTT). It is a joint collaborative training initiative between Varian Medical Systems, the University of Cape Town (UCT) and the Cape Peninsula University of Technology (CPUT) creating a program that links with the global Varian Access to Care program. Materials and methods: The first Access to Care course was preceded by a "dry run" course to test the curriculum. This consisted of three participants per team, who attended a physics course (physicists and RTTs) followed by a clinical course (including Radiation Oncologists). The feedback from participants resulted in the physics and clinical courses being conflated into a three-week integrated course for the treatment team members. Specific recommendations included additional time for practical planning; and, for all to attend equipment procurement sessions. The integrated A2C course (Aug–Sept 2015) consisted of three weeks at the centre followed by a three-month mentorship of participant teams. Four teams (RO, MP & RTT) attended and the twelve participants evaluated the course by completing surveys before, during and after the course. Consent was given to use this information. Results: In the post-course survey, participants indicated a 25% improvement in familiarity with immobilisation devices. Imaging and localisation improved by 41% and 3-D planning familiarity improved by 30%. The technology, Eclipse and VERT, was found to enhance participants' learning. Conclusion: Challenges identified were existing hierarchical structures, team work and financial constraints. Participants have been asked to comment on the mentorship process.